2013
DOI: 10.1145/2499947.2492686
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative learning instructional methods for CS1

Abstract: Cooperative learning is a well-known instructional technique that has been applied with a wide variety of subject matter and a broad spectrum of populations. This article briefly reviews the principles of cooperative learning, and describes how these principles were incorporated into a comprehensive set of cooperative learning activities for a CS1 course. In each activity, specific roles are assigned to group members in order to highlight important concepts and to enhance the overall functioning of the group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…With the field of computer science education maturing, educators are gaining access to a growing knowledge base of solid findings to guide them through making judicious decisions regarding teaching interventions. For example, there is robust evidence that pair programming and related cooperative learning instructional techniques lead to improvements in students' performance, self-efficacy and perceptions [Braught et al 2011;Beck and Chizhik 2013]. At the same time, welldocumented previous efforts give educators the resources as well as the confidence to apply "non-traditional" pedagogical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the field of computer science education maturing, educators are gaining access to a growing knowledge base of solid findings to guide them through making judicious decisions regarding teaching interventions. For example, there is robust evidence that pair programming and related cooperative learning instructional techniques lead to improvements in students' performance, self-efficacy and perceptions [Braught et al 2011;Beck and Chizhik 2013]. At the same time, welldocumented previous efforts give educators the resources as well as the confidence to apply "non-traditional" pedagogical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to the research focus of the present study, their analysis indicated that novice programmers perform better with Python-style syntax compared to C-style syntax and identified syntactic elements that are most problematic for learners. Beck and Chizhik [2013] also employed a robust methodology in order to compare traditional teaching methods and cooperative learning techniques using control groups and final grades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A pesar de que, como se menciona en la Sección 2, la literatura especializada establece diferencias entre el aprendizaje colaborativo y el aprendizaje cooperativo, algunos de los estudios reportados [22], [25], [27], [41], [51], [55], [60] manejan indistintamente estos conceptos. Mediante una revisión detallada se evidenció que el enfoque de estos estudios es más hacia el aprendizaje colaborativo, objeto del presente estudio, por lo que se decidió mantenerlos como fuentes primarias de datos para la revisión sistemática.…”
Section: Enfoque De Aprendizaje Y Tipos De Estudiosunclassified
“…Se presenta un enfoque específico de esta técnica orientado a disciplinas de las ciencias, la tecnología, la ingeniería y las matemáticas denominado POGIL -Process-Oriented Guided Inquiry Learning. POGIL es una estrategia centrada en el estudiante; los estudiantes trabajan en pequeños grupos con roles individuales para asegurar que todos estén completamente involucrados en el proceso de aprendizaje [22], [51]. Sistema de discusión en línea gamificado Es el componente de discusión de un CSCL al que se le han agregado elementos gamificados.…”
Section: Juego De Rolesunclassified
“…The search through the magazines and conference reports on computer science education (ACM Transaction on Computing Education, Computer Science Education, Journal of Educational Computing Research, Special Interest Group Computer Science Education Bulletin) provided findings related to computer science education in regard to constructivist teaching activities (Mark and Grissom, 2001), the "eXtreme teaching" approach (Andersson and Bendix, 2006), holistic teaching and learning (Thota and Whitfield, 2010), the influence of instructional methods on the design of computer programs (Hung, 2012), the effect of games on motivation in teaching (Freitas and Freitas, 2013), the reduction of learning content (Kilpeläinen, 2010), the application of formal modeling (Barnett and Windley, 2006;Carro et al, 2013), the effectiveness of two-person team programming (Braught et al, 2011), the effectiveness of cooperative learning instructional methods (Beck and Chizhik, 2013) and the application of the experiment (Schulte, 2012).…”
Section: Introductionmentioning
confidence: 99%